Aperture and permeability of aged concrete joints. (8th November 2021) - Görtz, J.; Zafar, A.; Wieprecht, S.; Terheiden, K.
Abstract: Often concrete structures cannot be regarded as monolithic since discontinuities like cracks and joints develop inevitably during construction and service life. Joints are not only introduced coincidentally at interfaces of different concreting steps, they are also induced deliberately to release stresses due to thermal actions or shrinkage in a controlled manner. This results in a change of material properties at the joint and is often investigated from a mechanical point of view. However, joints are also changing locally the moisture transport properties of a structure and thus considerably affecting the durability of those. Given the lack of data in the literature, in the presented work the distribution of the joint aperture and hydraulic conductivity is measured for a set of aged concrete expansion and cold joints. It is shown that the distribution of the apertures can be modeled with common probability distribution functions, which allow a relation between saturation and capillary potential. The parallel plate model is found to be a good estimate for the hydraulic conductivity of the joints when the available void areas of the joint are considered. Highlights: Measurement of the hydraulic conductivity and joint aperture of concrete joints. Evaluation of the distribution of joint aperture and void space along the joint. Estimation of the hydraulic conductivity based on measured joint apertures. Modeling of the aperture distribution by using probability density functions.